(untitled) (Международный научный журнал «Инженер», 2026)
This article analyzed the surfactants used to wash hydrotransport pipes of hosi divisor dispersing systems in the enrichment process of the mining industry. During the research work, the problem of creating polymer compositions that prevent blockage of solid particles in the flow process and the scientific justification of their effect on pressure was considered. New materials have been developed for hydrotransport systems with the aim of improving the efficiency of polymer compositions, ensuring long-term operation of the system and eliminating accumulations in pipes. The study explores the mechanical properties of polymer and composite materials, their effects on pressure and washing processes, as well as the strength and durability of materials to long-term performance. It helps to increase the performance of polymer compositions, hydrotransport pipes, accelerate washing processes and reduce energy consumption. The scientific basis of the study is carried out by analyzing the physicochemical properties of polymer compositions and external factors affecting them. New polymer compositions make it possible to increase the hydraulic and economic efficiency of hydrotransport systems, to extend their service life.